Left ventricular dyssynchrony and post-systolic shortening in young bodybuilders using anabolic-androgenic steroids - Grandperrin, Antoine; Schuster, Iris; Rupp, Thomas; Izem, Omar; Obert, Philippe; Nottin, Stéphane (American journal of physiology. Heart and circulatory physiology, 2021)
Left ventricular (LV) remodeling, characterized by increased LV hypertrophy and depressed systolic and diastolic function, is observed in strength-trained athletes who use anabolic-androgenic steroids (AAS). Previous studies suggested a pathological remodeling with an increase in cardiac fibrosis in these athletes, which could promote intraventricular dyssynchrony. In this context, this study evaluated LV dyssynchrony in strength-trained athletes using AAS, hypothesizing that the use of AAS would lead to an increase in post-systolic shortening. Forty-four male subjects (aged 20-40 yr) were divided into three age-matched groups: strength-trained athletes using (users, n = 14) or not (nonusers, n = 15) AAS and healthy sedentary men (controls, n = 15). After completing a survey, each participant was assessed with two-dimensional (2D)-strain echocardiography. LV dyssynchrony was quantified using the standard deviation (SD) of the time to peak for longitudinal strain of the 18 LV-segments (from the apical 4, 3, and 2 chambers views), the longitudinal strain delay index (LSDI), and the segmental post-systolic index (PSI). Users showed mean AAS dosages of 564 ± 288 mg[Formula: see text]wk-1 with a mean protocol duration of 12 ± 6 wk and a history of use of 4.7 ± 1.8 yr. They exhibited a greater LV mass index and depressed systolic and diastolic function when compared with both nonusers and controls. The decrease in LV strain in users was predominantly observed at the interventricular septum level (-16.9% ± 2.5% vs. -19.2% ± 1.8% and -19.0% ± 1.6% in users, nonusers, and controls, respectively, P < 0.01). Users showed higher SD than controls (43 ± 8 ms vs. 32 ± 5 ms, respectively, P < 0.01). The LSDI was significantly higher in users compared with both nonusers and controls (-23.4 ± 9.5 vs. -15.9 ± 9.3 and -9.8 ± 3.9, respectively, P < 0.01). PSI, calculated on the basal inferoseptal, basal anteroseptal, and basal inferolateral segments, were also greater in users compared with the two other groups. Our results reported an increase in LV dyssynchrony in young AAS users that brought new evidences of a pathologic cardiac remodeling in this specific population.NEW & NOTEWORTHY Illicit androgenic anabolic steroids (AAS) use is widespread, but data on LV dyssynchrony are lacking, although it could be increased by a higher prevalence of myocardial fibrosis reported in this population. In AAS users, the decrease in LV strain was predominantly observed in interventricular segments. All dyssynchrony indices were higher in AAS users and several segments exhibited post-systolic shortening. These results showed an association between AAS consumption, LV remodeling, and dyssynchrony.Left ventricular (LV) remodeling, characterized by increased LV hypertrophy and depressed systolic and diastolic function, is observed in strength-trained athletes who use anabolic-androgenic steroids (AAS). Previous studies suggested a pathological remodeling with an increase in cardiac fibrosis in these athletes, which could promote intraventricular dyssynchrony. In this context, this study evaluated LV dyssynchrony in strength-trained athletes using AAS, hypothesizing that the use of AAS would lead to an increase in post-systolic shortening. Forty-four male subjects (aged 20-40 yr) were divided into three age-matched groups: strength-trained athletes using (users, n = 14) or not (nonusers, n = 15) AAS and healthy sedentary men (controls, n = 15). After completing a survey, each participant was assessed with two-dimensional (2D)-strain echocardiography. LV dyssynchrony was quantified using the standard deviation (SD) of the time to peak for longitudinal strain of the 18 LV-segments (from the apical 4, 3, and 2 chambers views), the longitudinal strain delay index (LSDI), and the segmental post-systolic index (PSI). Users showed mean AAS dosages of 564 ± 288 mg[Formula: see text]wk-1 with a mean protocol duration of 12 ± 6 wk and a history of use of 4.7 ± 1.8 yr. They exhibited a greater LV mass index and depressed systolic and diastolic function when compared with both nonusers and controls. The decrease in LV strain in users was predominantly observed at the interventricular septum level (-16.9% ± 2.5% vs. -19.2% ± 1.8% and -19.0% ± 1.6% in users, nonusers, and controls, respectively, P < 0.01). Users showed higher SD than controls (43 ± 8 ms vs. 32 ± 5 ms, respectively, P < 0.01). The LSDI was significantly higher in users compared with both nonusers and controls (-23.4 ± 9.5 vs. -15.9 ± 9.3 and -9.8 ± 3.9, respectively, P < 0.01). PSI, calculated on the basal inferoseptal, basal anteroseptal, and basal inferolateral segments, were also greater in users compared with the two other groups. Our results reported an increase in LV dyssynchrony in young AAS users that brought new evidences of a pathologic cardiac remodeling in this specific population.NEW & NOTEWORTHY Illicit androgenic anabolic steroids (AAS) use is widespread, but data on LV dyssynchrony are lacking, although it could be increased by a higher prevalence of myocardial fibrosis reported in this population. In AAS users, the decrease in LV strain was predominantly observed in interventricular segments. All dyssynchrony indices were higher in AAS users and several segments exhibited post-systolic shortening. These results showed an association between AAS consumption, LV remodeling, and dyssynchrony.